Avaliação da presença de fator de risco de morbidade em lactentes matriculados em creche no município de São Paulo - Konstantyner, Tulio [UNIFESP] (2009)
The present cross-sectional study aims at identifying and quantifying risk factors for anemia in 212 infants enrolled in two public and three philanthropic day care centers in São Paulo city. Interviews with the mothers, collection of blood by digital punction and anthropometry were performed. When the hemoglobin was lower than 11g/dl it was considered anemia. A logistic regression model for risk factors between groups of infants with and without anemia was adjusted. Statistical softwares Epi Info 2000 and Stata 8.0 were used. The prevalence of anemia was 51.9%. The final logistic model comprised 4 variables assign by hierarchic standard: presence of one or more siblings under 5 years old (OR=2.57/p=0.005), to attend exclusively public managed day care centers (OR=2.12/p=0.020), exclusive maternal breast feeding for less than 2 months (OR=1.88/p=0.044), age under 15 months (OR=2.32/p=0.006). We concluded that the high prevalence of anemia found evidences the difficulty of the studied day care centers system regarding control and prevention of such nutritional failure, therefore it should be the health planner’s responsibility to consider the risks for anemia identified and quantified by the time the control and prevention programs are elaborated.